Pengembangan LKPD Berbasis Inkuiri Terbimbing Pada Materi Sistem Pencernaan di SMAS Katolik St. Gabriel - Ratna Susana Dawa; Yohanes Nong Bunga; Yohanes Bare (Peneliti.net, 2021)
This study aim to develop student worksheets based on guided inquiry on the human digestive system material. This research is a development research that adapts the 4D development model. The research instrument used is a questionnaire and documentation. The product developed was validated by material, media and language experts and then tested on a small and large scale, namely two biology teachers and thirty-four students of class XI MIA of SMAS Katolik Sint Gabriel Maumere. Based on the results of the validator of the student worksheets the digestive system was declared very valid and the responses of teachers and students concluded that the student worksheets developed was suitable to be used as a learning resource, especially biology subjects